Baduanjin improves neck pain and functional movement in middle-aged and elderly people: A systematic review and meta-analysis of randomized controlled trials - Liu, Zicai; Hu, Hao; Wen, Xin; Liu, Xuejin; Xu, Xiaqing; Wang, Zhenjiang; Li, Li; Liu, Huiyu (Frontiers in Medicine, 2023)
Abstract: Objective: We conducted a systematic review and meta-analysis to investigate the efficacy of Baduanjin for middle-aged and old patients with Neck Pain (NP). Methods: Two researchers collectively searched the PubMed, Web of Science, Embase, Cochrane Library, China Biology Medicine disc (Sino- Med), China National Knowledge Infrastructure (CNKI), Wan Fang database, and China Science and Technology Journal Database (VIP). The search time is set from initial to February 2022 to find out articles that may meet the criteria. The risk bias assessment tool Cochrane was be applied to assess the methodological quality of involved studies. Review Manager 5.3 was applied to statistical analysis of all data. Results: Nine randomized controlled trials in total were meta-analyzed, including 560 patients. The results turned out that the VAS score in the intervention group was below the control group, which was statistically significant [MD = -0.94, 95% CI (-1.33, -0.54) and P <0. 00001]. The result of general efficiency suggests that the baduanjin was better than the conventional therapy [RR = 1.18, 95% CI (1.08, 1.30), P= 0. 0004]. Conclusion: Baduanjin exercise can significantly relieve the neck pain of middle-aged and elderly people and significantly improve the clinical symptoms, which is worth promoting globally and a good choice for home health care. This systematic review preliminarily provides evidence-based medical evidence of baduanjin in the treatment of middle-aged and elderly patients with neck pain, and provides decision-making basis for clinical and home treatment of these patients with neck pain.